The Role and Value of Ongoing and Peer Support in Diabetes Care and Education. Issue 6 (December 2019) - Warshaw, Hope; Hodgson, Lisa; Heyman, Mark; Oser, Tamara K.; Walker, Heather R.; Deroze, Phyllisa; Rinker, Joanne; Litchman, Michelle L.
Purpose: Increasing attention is being given to the challenges and emotional toll of managing diabetes. This Perspectives in Practice details the specialty's guiding documents for initial and ongoing support. It also defines various types of social support, including peer support, for optimal diabetes care. Focusing on peer support, this paper provides a review of the body of evidence demonstrating the value of peer support to improve clinical and behavioral outcomes. To achieve positive outcomes, it is optimal for people with diabetes to have access to ongoing support from their health care provider, including diabetes care and education specialists. They should also be made aware of, and given referral to options and opportunities for peer support. This Perspectives in Practice concludes with a call to action for diabetes care and education specialists to deliver to integrate and promote the value of peer support in the care they provide. Conclusion: Managing diabetes during the stages and ages of life is chronically challenging and complex. Various types of support offered by health care providers, including diabetes care and education specialists and others in the person's social support milieu, can positively affect emotional well-being. Health care providers should routinely assess their client's social supports and refer the person with diabetes and/or their caregivers to evidence-based types of peer support mutually determined to be of most value. Diabetes care and education specialists should increase their awareness of opportunities to integrate the value of and referral to peer support in their counseling and to gain greater insight into the diabetes-lived experience.